Risks and Adaptation Strategies for Disaster Readiness: Basis for School Sustainability Plan - Aquino, Rayver C.; Polintan, Ramil P.; Mones, Erlinda C.; Subia, Gener S. (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study was conducted to determine the risks and adaptation strategies for disaster readiness as a basis for the school sustainability plan of eight (8) medium public elementary schools in Licab District, Nueva Ecija with the use of descriptive-correlational research design. A total of 103 employees served as respondents of the study. The yearly disasters encountered by the school employees are floods and typhoons. They are aware of flood risks thus, they always ensure the safekeeping of school records. As to their experience in a typhoon, "their understanding of the warning signal was very evident and always adopt measures of disaster prevention and facilitate the immediate resumption of classes. In their risk adaptation strategies, the respondents prepare the best response during an emergency, they know the emergency hotline numbers, they are aware of the emergency evacuation plan and they actively joined any disaster prevention, relief action, or emergency drill. As to their knowledge about the disaster, the respondents always get information from TV or Radio, electronic messages (Mobile SMS, etc.), and social networking sites (e.g. Facebook, Twitter). In terms of their readiness, they claimed that they always: have medication and first aid kit ready and store emergency kits or Go bag (including documents, water, foods, flashlight or candle, radio, cellphone, rope and etc.). The risk adaptation strategies of the respondents were positively related to their disaster readiness which implies that activities such as conducting drills, emergency plans, and attending seminars and trainings increase the preparedness for a disaster of the respondents.